Detection of Breast Cancer in an FDG-PET Cancer Screening Program: Results of a Nationwide Japanese Survey - Minamimoto, Ryogo; Senda, Michio; Jinnouchi, Seishi; Terauchi, Takashi; Yoshida, Tsuyoshi; Inoue, Tomio (Clinical breast cancer, 2015)
“FDGPET cancer screening program” is defined as a cancer screening program using FDG-PET with or without a combination of other tests, that is aimed at the detection of cancer at an early stage. The FDG-PET screening program detected 161 breast cancers in 62.054 asymptomatic subjects, and 83.0% of them was detected at Stage 0 or I. The [18F]-fluorodeoxyglucose positron emission tomography (FDG-PET) cancer screening program is defined as cancer screening for asymptomatic subjects using FDG-PET/computed tomography with or without combination of other screening tests. The aim of this study was to analyze the detection rate and effectiveness of the FDG-PET cancer screening program for breast cancer between 2006 and 2009 in Japan. A total of 62,054 asymptomatic female subjects underwent FDG-PET cancer screening. We analyzed 473 cases with findings of possible breast cancer in any screening tests. Among 473 possible cases, 161 were verified as breast cancer. The relative sensitivity and positive predictive value (PPV) of FDG-PET for breast cancer were 83.9% and 41.7%, respectively. The relative sensitivity and PPV of mammography (MMG) for breast cancer was less than for FDG-PET; results for breast ultrasonography (US) were close to FDG-PET. The combination of FDG-PET with MMG and US might contribute to increased sensitivity but does not improve PPV. Most breast cancer cases (83.0%) detected using the FDG-PET cancer screening program were stage 0 or I based on the Union for International Cancer Control criteria. The FDG-PET screening program in Japan detected breast cancer at an early stage. A combination of FDG-PET and MMG and/or breast US yields the best results for detecting breast cancer. The FDG-PET cancer-screening program alone cannot detect all breast cancers.